OP0106 Who is not reaching remission in early ra and why? predictors for persistent disease activity in the first year differ in men and women and are related to lifestyle and treatment. (12th June 2018) - Bartlett, S.J; Schieir, O.; Valois, M.-F.; Hitchon, C.; Boire, G.; Haraoui, B.; Thorne, C.; Tin, D.; Pope, J.; Keystone, E.C.; Bykerk, V.P.; ,
Abstract : Background: Although early identification and aggressive treatment of RA improves outcomes, we have shown that 45% of early RA participants receiving guideline-based care do not achieve remission in the first year. Moreover, fewer women reached remission than men. Objectives: To compare predictors of persistent disease activity (LDA/MDA/HAD) in the 1 st year of RA treatment in men and women. Methods: Sample included adults in CATCH (Canadian Early Arthritis Cohort) from 2007–2016 with active disease at baseline and ≥12 m F/U. Standardised visits included clinical assessments, questionnaires, and lab tests. Logistic regression with backward selection was used to identify predictors of failing to achieve remission (DAS28 <2.6) by 12 months among baseline sociodemographic and RA characteristics and patient reported outcomes. Results: The sample included 1628 adults with classifiable RA, who were mostly female (72%) with a mean (SD) age of 55, (15) with 2 (2) comorbidities, and symptom duration of 6 (3) months. At enrollment, 95% had active disease (DAS28 MDA (42%); HDA (53%)), most were initially treated with csDMARDS (any 92%; MTX 75%). 46% of women and 38% of men did not reach remission by 12 months. Among women, multivariable results showed obesity more than doubled the likelihood of not achieving remission; other key predictors were minority status, lower education, and higher TJC and fatigue scores at baseline (table 1). In men, current smoking was associated with a 3.5 greater odds of not achieving remission in the first year; other predictors included older age, and higher pain. Not using MTX increased the likelihood of not achieving remission in women by 28% and men by 45%. Longer symptom duration and higher ESR were associated with not achieving remission in all. Factors not related to persistent disease activity included family history of RA, RF/ACPA status, erosions, SJC, HAQ and depressive symptoms at baseline. Conclusions: In this large pan-Canadian cohort of early RA patients receiving guideline-based arthritis care, obesity in women and current smoking in men were the strongest predictors of not achieving remission in the first 12 months followed by non-use of MTX, higher baseline inflammation and longer symptom duration. Additional poor prognostic indicators in women included minority status, lower education, and higher fatigue, whereas older age and greater pain were associated with persistent disease activity in men. Smoking cessation in men and weight reduction in women, and optimising MTX use may facilitate rapid reduction of inflammation, an essential goal of treatment in early RA. Acknowledgements: Sponsors: Amgen & Pfizer-Founding sponsors 2007+; UCB, AbbVie 2011+; Medexus 2013+; Eli Lilly, Sanofi- Genzyme 2016+; Merck 2017+; BMS 2011–2014, Hoffmann-LaRoche, Janssen 2011–2016 Disclosure of Interest: None declared